a) (x + 1)(x + 4)
b) 2(2x + 3)(2x – 1)
c) –(x + 7)(x – 3)
d) 1 – (z + 5)(z – 1)
e) 2k [kwadrat] – (k + 3)(2k + 4)
f) -3(a + 2b)(a – b) [kwadrat]
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a) (x + 1)(x + 4)=
=x²+4x+x+4
b) 2(2x + 3)(2x – 1)=
=2(4x²-2x+6x-3)=
=8x²-4x+12x-6=
=8x²+8x-6
c) –(x + 7)(x – 3)=
=-(x²-3x+7x-21)=
=-(x²+4x-21)=
=-x²-4x+21
d) 1 – (z + 5)(z – 1)=
=1-(z²-z+5z-5)=
=1-z²+z-5z+5=
=-z²-4z+6
e) 2k² – (k + 3)(2k + 4)=
=2k²-(2k²+4k+6k+12)=
=2k²-(2k²+10k+12)=
=2k²-2k²-10k-12=
=-10k-12
f) -3(a + 2b)(a – b)²=
=-3(a+2b)(a²-2ab+b²)=
=-3(a³-2a²b+ab²+2a²b-4ab²+2b³)=
=-3(a³-3ab²+2b³)=
=-3a²+9ab²-6b³